Analisis Pendapatan Usahatani Hidroponik Utama Hidrofarm Di Minahasa Utara - Amar; Rumangit, Grace Adonia Josefina; Paulus, Jeanne (Sam Ratulangi University, 2023)
This research aims to analyze the revenue from the hydroponic Utama Hidrofarm business, and to know how effective the hydroponic farming of Utama Hidrofarm as a business. This research was conducted for 2 months, from March to April 2022 at Utama Hidrofarm ini North Minahasa District, Dimembe District. Data collection was carried out through interviews with the owner of the Utama Hidrofarm hydroponic farming for primary data, and for secondary data which is data collection and research materials obtained through the Google for thesis, journals, and other sources related to the issues discussed in this study. Analysis can be used to determine the main business income of Utama Hidrofarm in North Minahasa. Based on the results of the research done then it is known that from total revenue of IDR562.500 / day after reduced costs incurred in the form of variable costs and fixed costs totaling cost IDR528.070 / day then the result of hydroponic farming of the main reduction of the main reduction of Nina Minahasa Nina hyprofar can earn revenues of IDR34.430 / day for 45 days of planting period. For green vegetables from total reception of IDR2.250.000 / day after reduced production costs at a total cost IDR1.406.560 / day then the result of hydroponic farming of the main green vegetable hydrophone marriage of Minahasa Nina Mosaharbarity may earn revenues of IDR843.440 / day for 45 days of planting period.